A dataset of necrotized cassava root cross-section images - Nakatumba-Nabende, Joyce; Akera, Benjamin; Tusubira, Jeremy Francis; Nsumba, Solomon; Mwebaze, Ernest (Data in brief, 2020)
Cassava brown streak disease is a major disease affecting cas- sava. Along with foliar chlorosis and stem lesions, a very common symptom of cassava brown streak disease is the development of a dry, brown corky rot within the starch bearing tuberous roots, also known as necrosis. This paper presents a dataset of curated image data of necrosis bearing roots across different cassava varieties. The dataset contains images of cassava root cross-sections based on trial harvests from Uganda and Tanzania. The images were taken using a smartphone camera. The resulting dataset consists of 10,052 images making this the largest publicly available dataset for crop root necrosis. The data is comprehensive and contains different variations of necrosis expression including root cross-section types, number of necrosis lesions, presentation of the necrosis le- sions. The dataset is important and can be used to train ma- chine learning models which quantify the percentage of cas- sava root damage caused by necrosis.
Keywords: Cassava; CBSD; Necrosis; Lesions; Cassava root cross-sections